Economic impact of road accidents on costs of employee turnover: A quantitative study from Poland - Agata Małgorzata Jaździk-Osmólska; Magdalena Kalbarczyk Kalbarczyk; Daniel Trzaskowski; Robert Wojtachnik; Adrianna Trzaskowska-Dmoch (Archives of Transport)
The article presents the results of the Polish research in 2014 and 2020 involving economic loss in enterprises due to employees' work disability due to road accidents. Road safety is one of the most essential global declines in social health, but marginal external road transport costs are not easy to measure. Typically, the aspect of risk in road safety in the operations of enterprises is viewed in the context of transport or logistic companies. However, the risk of becoming a road accident victim is not limited to fleet drivers. Better information about employee road accident costs needs to be provided in the literature. The Polish research shows that employees' work disability due to road accidents is extremely costly, often more than one would expect. A decrease in the risk of death in road safety in Poland in 2014-2019 did not reduce the costs to enterprises, which grew from PLN 1.1 million to PLN 1.6 million. Management of economic loss in enterprises due to road accidents is essential not only from the financial point of the organisation but also from the idea of corrective instruments to equate marginal social costs with marginal social benefits of transport The results of the conducted research bridge the research gap, vital from the point of view of community and corporate operations, regarding the volume of losses of enterprises due to employee turnover due to road accidents, which are likely to affect any. Further research should aim at specific conditions of minimizing employer losses discussed here, e.g. in the area of health policy improvement, which would allow a faster personal and professional recovery. The issue of the employer's employee social policy regarding creating suitable conditions for taking out life insurance is crucial. Ultimately, it is worth looking closer at employees' willingness to buy insurance coverage if the risk of a loss of life or health due to a road accident is real and substantial. Moreover, results show the critical direction for business – corporate social responsibility for road safety. It is warranted that further research should focus on recognizing and enhancing this role.